Coastal zone management in India − present status and future needs. Issue 2 (3rd April 2017) - Nayak, Shailesh
Abstract: The coastal zone is a region where land, ocean and atmosphere interact and hence it is dynamic in nature. India has a long coastline which was not adequately monitored until the advent of the satellite remote sensing era in the 70s. India has a very robust remote sensing program that the Indian Remote Sensing Satellite (IRS) series of satellites were effectively used to monitor coastal habitats, landforms, shoreline, water quality, etc., and changes were identified during the last 40 years. The classification system for coastal habitats and the classification and geometric accuracies of products were standardized. Detailed information for mangroves communities and characteristics of coral reefs were generated. The high and low tide lines were delineated seamlessly for the entire coastline using satellite data. All these data were organized in a GIS and the coastal database for the entire country was created. Impacts of various hazards on such as cyclones, tsunami and sea level changes on coastal habitats were documented. Based on topography, shoreline changes and tides, coastal multi-hazard vulnerability maps were characterized by employing the elevation data derived from satellite data and were prepared for the coastline of India. The information on ocean color and sea surface temperature was used to generate potential fishery advisories, which are provided daily to fishermen. The coastal database was utilized effectively to identify coastal regulation zones, marine protected areas, vulnerable zones, etc. Various services for tsunami, fishery and coral reef bleaching were generated for societal benefits. It is planned to develop models for the coastal zone, so that impeding dangers and likely changes in the coastal zone can be predicted and suitable actions can be undertaken. It is necessary to integrate socio-economic data with the knowledge database of coastal zone to understand the impact of anthropogenic activities and the changing climate on the coastal zone.